1925
DOI: 10.1017/s0368393100133930
|View full text |Cite
|
Sign up to set email alerts
|

The Flight of Birds

Abstract: 1. The object of this paper is to explain the principles upon which the flapping flight of birds depend and to show how the velocities, power expended and gliding angles can be approximately calculated. The birds are considered to be flying on a horizontal course with constant velocity. The calculations have been made for five birds, the Teal, the Grouse, the Common Swift, the Starling and the Stork, but the formulae given can of course be used for any bird.2. The results obtained seem to show that:—1st.—As re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1951
1951
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…required slightly less than &th horse-power in level flight. A re-examination of the data by Fullerton (1925), who assumed that all the work was done on the downstroke, confirmed Lilienthal's figure and showed that at about 32 miles per hour the power required was a minimum. Gnosspelius (1925), working with different wing sections, calculated a power requirement of 0.052 horsepower at this speed.…”
Section: Quantitative Analysis Of F L I G H Tmentioning
confidence: 72%
“…required slightly less than &th horse-power in level flight. A re-examination of the data by Fullerton (1925), who assumed that all the work was done on the downstroke, confirmed Lilienthal's figure and showed that at about 32 miles per hour the power required was a minimum. Gnosspelius (1925), working with different wing sections, calculated a power requirement of 0.052 horsepower at this speed.…”
Section: Quantitative Analysis Of F L I G H Tmentioning
confidence: 72%
“…Here the author has attempted from his empirical knowledge of the properties of fixed wings to calculate the characteristics of a stork, and comes to the conclusion that such a bird weighing 4 kilograms must have a power output of slightly less than 1/10 horse-power. This work was extended by Fullerton (1925) who, assuming that all useful work was done on the down-stroke, calculated various parameters of the flight. He concluded that the speed requiring least work was 32.5 miles per hour, and the power required was 57 foot-pounds per second or 1/10 horse-power.…”
Section: Z B ?mentioning
confidence: 99%